Cultural and Social Bias Leading to Prenatal Sex Selection: India Perspective - Chakravarty, Nayan; Dabla, Vandana; Sagar, Moni; Neogi, Sharmila; Markan, Mridu; Segan, Mehak; Agnani, Shilpi; Kapahi, Pooja; Neogi, Sourav (Frontiers in Global Women's Health, 2022)
Globally, 23.1 million missing female births have been documented, resulting in an imbalanced sex ratio at birth (SRB) between the late 1990s and 2017, with India accounting for almost half of this missing women population. While the country is progressively taking measures to enhance women's position in society and implementing policies toward augmenting the value of a girl child, some deeply rooted cultural and social beliefs propel a strong son preference, resulting in active daughter discrimination. The continuance of patriarchal norms and inequitable gender roles, resulting in son preference, fertility decrease, and reduction in preferred family sizes, and technical breakthroughs that allow for the identification of the sex of the fetus, is all connected to distortions in the sex ratio at birth. Son preference is a well-documented phenomenon in India, and its implications for skewed gender ratios, female feticide, and higher child mortality rates for girls have piqued researchers' and policymakers' interest. The fundamental factors of son preference as an ideology are less widely investigated. With this objective, an extensive secondary review was conducted of the socio-cultural norms and biases leading to increased prenatal sex selection in India despite the laws against it. The study findings suggest that it is imperative to emphasize the necessity for consistent and collective efforts from all stakeholders: changing the social perception of the value of girls requires collective effort and the equal participation of all stakeholders, including civil society organizations and the local community.